2017
DOI: 10.1016/j.fertnstert.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes after natural conception versus in vitro fertilization (IVF) in gestational surrogates: a model to evaluate IVF treatment versus maternal effects

Abstract: Neonates born from commissioned embryos and carried by gestational surrogates have increased adverse perinatal outcomes, including preterm birth, low birth weight, hypertension, maternal gestational diabetes, and placenta previa, compared with singletons conceived spontaneously and carried by the same woman. Our data suggest that assisted reproductive procedures may potentially affect embryo quality and that its negative impact can not be overcome even with a proven healthy uterine environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 45 publications
(33 reference statements)
4
43
0
3
Order By: Relevance
“…The reasons for disapproval were similar to those for gamete donation. Gestational surrogacy has been reported to increase adverse perinatal outcomes, including preterm birth, low birth weight, hypertension, gestational diabetes, and placenta previa, compared with spontaneous pregnancy by the same women [ 12 ]. These were not mentioned, however, as reasons for disapproval in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for disapproval were similar to those for gamete donation. Gestational surrogacy has been reported to increase adverse perinatal outcomes, including preterm birth, low birth weight, hypertension, gestational diabetes, and placenta previa, compared with spontaneous pregnancy by the same women [ 12 ]. These were not mentioned, however, as reasons for disapproval in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study pregnancy complications and perinatal outcomes were compared in live born singletons conceived with the use of embryos from intended parents (n =103) versus SC (n = 249) carried in the same woman (Woo et al 2017). Children born after GS had a lower mean gestational duration, higher rates of PTB (10.7% versus 3.1%, respectively), and higher rates of LBW (7.8% versus 2.4%, respectively).…”
Section: Gestational Surrogacymentioning
confidence: 99%
“…Children born after GS had a lower mean gestational duration, higher rates of PTB (10.7% versus 3.1%, respectively), and higher rates of LBW (7.8% versus 2.4%, respectively). The authors concluded that the results showed that ART may potentially affect embryo quality and that even a proven healthy uterine environment cannot compensate for this negative impact (Woo et al 2017). However, many factors might have affected the study outcome, for example an artificial replacement cycle versus natural cycle, number of embryos transferred, and the time interval between the SC and surrogate pregnancies (Spandorfer 2017).…”
Section: Gestational Surrogacymentioning
confidence: 99%
“…On the other hand, the top reasons for not approving were that familial relations are unnatural and that pregnancy should be natural. Gestational surrogacy has been reported to increase adverse perinatal outcomes, including preterm birth, low birth weight, hypertension, gestational diabetes, and placenta previa, compared with spontaneous pregnancy by the same women [12]. Although this fact can be a reason for not approving of gestational surrogacy, it was not main reason for disapproval in this study.…”
Section: Discussionmentioning
confidence: 53%